Засоби масової інформації у процесі організаційної комунікації - Зозуля, Наталія (Видавництво Львівської політехніки, 2016)
The work observes features selection of Media for organizations and their employees; reviews the research-based knowledge regarding organizational communications, a complex process that is vital to organizational success in a dynamic global marketplace. It analyzes important issues in current practice–social media, draws attention to the new social media, that facilitate a “powerful global conversation” in which everyone can participate and share opinions, ideas, knowledge and images with each other, and circumvent traditional dogmas.
Keywords: communications; media; new social media; information; professional communicators